The relationship between health beliefs and stroke preventive behaviors in Diabetes Mellitus patients with hypertension - Compichai, Pantip; Khungtumneam, Kamontip; Kompayak, Jariyawat (Thai Journal of Nursing, 2022)
This research aimed to study the relationship between health beliefs and stroke preventive behaviors in diabetes mellitus patients with hypertension. The sample consisted of diabetes mellitus patients with hypertension who came to receive services in Nongprue of Tambon Health Promoting Hospital, Samut Prakan province, purposively collected 110 people. Research tools were questionnaires on stroke preventive behaviors, and health beliefs. Pass the validation check content oriented from 3 experts and content validity index [CVI] = .0875-1.000 The Cronbach’s alpha coefficients are equal to .867, .753, .718, .726, .768 and .700. The data is analyzed by mean, standard deviation, Spearman Rank Correlation, Mann-Whitney U Test, and Kruskal-Wallis H Test. The results showed that the sample group had overall stroke preventive behaviors at a moderate level ( = 3.35, SD = 0.333). There were significant factors associated with stroke preventive behaviors; marital status (KW = 9.688, p < .05), perceived severity of stroke (rs = .303, p < .001), perceived susceptibility of stroke (rs = .267, p < .01), perceived benefits to stroke preventive behaviors (rs = .249, p < .01), and perceived self-efficacy to stroke preventive behaviors (rs = .228, p < .05)